Antropometria e desempenho motor de atletas de Futebol de 7 - Rosch de Faria, Fernando (2018)
Introduction: The Football 7 is intermittent sport which strength capacity is evidenced, making the evaluation of this and other capacities essential for achievement of sporting performance. Objective: The aim of study was to identify the anthropometric profile and the motor performance of the athletes from the Brazilian National Cerebral Palsy Football Team. Methods: The sample was composed of 16 athletes. The Anthropometric assessment was: weight, height, BMI, skinfolds and waist circumference. To the motor performance was: vertical jump tests, 10x5 meters agility test and RAST test. Results: The anthropometric variables showed: body mass (Kg) was 69.6±7.3, BMI was 19.9±1.9, sum of 9 skinfolds 88.3±34.8 and body fat percentage was 10.6±5.4. The motor performance showed: the agility test was 18.9±1.1, the countermovement jump was 33.4±8, the squat jump was 31.6±7.6 and average power was 6.3±1.5. Conclusion: The results showed suitable for high-performance athletes and the motor performance of them was influenced by their functional class.